PROSES PENETAPAN AHLI WARIS PENGGANTI Perkara Nomor 21/Pdt.P/2006/PA.Yk - , PUTRI NINDITASARI; , Hartini, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Islamic inheritance law has very important standing. Settlement Islamic inheritance is authority of Religious Court. In essence, issue of inheritance is steps in formulating inherited properties from the deceased to his heir. However, in its reality the process of transferring inherited property often deal with problem. Issue of inheritance often leads to dispute for heirs because it relates directly to oneâs property. Therefore author was interested to select title âDetermination Process of substituting heirâ, because of wanting to identify process of determining substituting heir in decision of Yogyakarta Religion Court at case number 21/Pdt.P/2006/PA/YK This Field working practice was intended to fulfill graduation requirement for Diploma 3 Law program, vocational school, GadjahMada University and to obtain degree AhliMadyaHukum. Benefit author get during field working practice is real experience as candidate professional employee. Author can share creativity in working world particularly in law field and apply knowledge obtained in class in working field in Yogyakarta Religion Court. Result of this final assignment report indicated that substituting heir system may occur when people relate directly to the grantor has died. The regulation is stipulated in Article 185 of the Islamic Law compilation explaining that (1) heir that dies before the grantor, their standing may be replaced by their son, except for them mentioned in article 173